Humour in interaction and cognitive linguistics: critical review and convergence of approaches - Buján Navarro, Marta (Complutense Journal of English Studies, 2019)
Linguistic humour studies have been undertaken from different perspectives. The present paper offers a review of the most influential theories seeking synergies and convergence between them under the umbrella of cognitive linguistics, and, more specifically, resorting to Langacker’s (2001) current discourse space (CDS) as the overall framework which can accommodate and encompass those perspectives, along with Fauconnier and Turner’s (2003) Conceptual Integration Theory. A sketch of various theories is included (Raskin, 1985; Attardo, 1994; Coulson, 2005a; Veale, 2015, etc.), along with an analysis of points of convergence and similarities as the rationale for bringing them together against the backdrop of the CDS.